Violence Against Women and Children, Vol 2: Navigating Solutions. 2011
DOI: 10.1037/12308-005
|View full text |Cite
|
Sign up to set email alerts
|

Services for victims of sexual violence.

Abstract: The purpose of this chapter is to review the literature on sexual assault victims' postassault help-seeking experiences with the medical and mental health systems (see Chapter 7, this volume, regarding victims' experiences with the legal system). It is beyond the scope of this chapter to delve into the literatures on secondary or tertiary mental health intervention research. By way of introduction, we begin by defining the key terms used in this chapter. Consistent with the definitions put forth by Koss and Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…First, putting the victim's welfare needs above the needs of the investigation may put British officers in conflict with the legal requirement to explore all reasonable lines of enquiry, including that the allegation is false (Criminal Procedure and Investigations Act, ). Second, it is increasingly the case that alternative arrangements exist to support victims, with the introduction in the UK of specially trained officers to act as victim chaperones and the establishment of specialist Sexual Assault Referral Centres (SARCs) focusing on victim welfare (Horvath et al ., ; Campbell & Patterson, ; Stern, ). Related to this, victims themselves may prefer to have “someone who was ‘there for them’, whose lack of involvement with evidence gathering meant they had more freedom to respond to each individual's needs and concerns” (Lovett et al ., , p.42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, putting the victim's welfare needs above the needs of the investigation may put British officers in conflict with the legal requirement to explore all reasonable lines of enquiry, including that the allegation is false (Criminal Procedure and Investigations Act, ). Second, it is increasingly the case that alternative arrangements exist to support victims, with the introduction in the UK of specially trained officers to act as victim chaperones and the establishment of specialist Sexual Assault Referral Centres (SARCs) focusing on victim welfare (Horvath et al ., ; Campbell & Patterson, ; Stern, ). Related to this, victims themselves may prefer to have “someone who was ‘there for them’, whose lack of involvement with evidence gathering meant they had more freedom to respond to each individual's needs and concerns” (Lovett et al ., , p.42).…”
Section: Discussionmentioning
confidence: 99%
“…Organisational factors are clearly important. The existence of Sexual Assault Referral Centres, where victims are examined in a sympathetic environment and can access medical and psychological care (Lovett, Regan, & Kelly, ; Campbell & Patterson, ), the quality of police training, the presence of specialist officers, and robust management and supervision are factors that may enhance the victim's experience and the effectiveness of evidence gathering. Similarly, the presence of rape victim advocates appears to improve the experience of victims, including the extent to which they were negatively treated by officers (Campbell, ).…”
Section: The Victim As a Means To An End: Detective Decision Making Imentioning
confidence: 99%
“…Indeed, since I wrote these early articles and although there is still substantial work that needs to be done, there has been increasingly greater support for services for victims of sexual violence, with a recent emphasis on coordinated community response interventions. Such Sexual Assault Response Teams ’ (SARTS) primary goal is to coordinate victim services so that they can obtain comprehensive care, regardless of where they first present (see Campbell & Patterson, 2011). Although such models warrant further investigation, these victim-centered responses hold promise for reducing trauma associated with victimization.…”
Section: Looking To the Futurementioning
confidence: 99%
“…6,14,15,16 For example, SANEs are taught in their training to collect cervico-vaginal specimens, which research has shown are more likely than other types of evidence swabs to be positive beyond 36 hours post-coitus. 17 This is in contrast to what would typically occur without a trained SANE evidence collector -where if collected, samples might well only include less helpful conventional vaginal swabs.…”
Section: The Role Of the Sexual Assault Nurse Examinermentioning
confidence: 99%
“…5 In stark contrast, when treated by SANEs, 97% were offered EC and 99% were treated for STIs. 6 Patients' care options should be consistent and not dependent upon the provider.…”
mentioning
confidence: 99%